Current trends in ACL reconstructions. A Perspective Review of Recent Literature - Brzoza, Joanna; Werenkowicz, Wiktor; Boral, Aleksandra; Kryś, Dominika; Koczur, Julia; Górski, Michał; Pniok, Wiktoria; Kurkiewicz, Wojciech; Bylica, Kinga; Czarnecki, Bartłomiej (Journal of Education, Health and Sport, 2025)
INTRODUCTION The anterior cruciate ligament (ACL) plays a vital role in maintaining knee stability and supporting physical activity. ACL injuries, whether due to trauma or overuse, are common in both athletes and the general population, often resulting in impaired function and an elevated risk of osteoarthritis. In recent years, ACL reconstruction techniques have evolved significantly due to advancements in medical technology, a deeper understanding of knee biomechanics, and a stronger focus on patient outcomes. This review integrates current evidence on surgical innovations, graft selection, and rehabilitation to guide clinicians in optimizing ACL reconstruction and improving patient quality of life. METHODS This review synthesizes literature from 2020 to 2025, focusing on ACL reconstruction techniques, graft selection, and adjunctive procedures. A systematic search was conducted using databases such as PubMed, Scopus, and Google Scholar with terms including "ACL reconstruction," "graft choices," and "rehabilitation protocols." Studies addressing surgical innovations and outcomes were included without exclusion criteria. AIM OF THE STUDY The aim is to synthesize and critically appraise current trends in ACL reconstruction based on recent evidence. CONCLUSION ACL reconstruction requires precise surgical technique, appropriate graft choice, structured rehabilitation, and psychological support. Autografts have shown favorable outcomes, while personalized rehab protocols enhance recovery. Addressing mental health during rehabilitation is also essential. Future strategies should focus on standardizing care, integrating psychological support, and exploring regenerative therapies. A multidisciplinary approach is key to improving outcomes and quality of life after ACL injuries.